A Multifrequency Census of 100 Pulsars below 100 MHz with LWA: A Systematic Study of Flux Density, Spectra, Timing, Dispersion, Polarization, and Its Variation from a Decade of Observations - Kumar, Pratik; Taylor, G.B.; Stovall, K.; Dowell, J.; White, S.M. (2025)
We present a census of 100 pulsars, the largest below 100 MHz, including 94 normal pulsars and six millisecond pulsars, with the Long Wavelength Array (LWA). Pulse profiles are detected across a range of frequencies from 26-88 MHz, including new narrowband profiles facilitating profile evolution studies, and breaks in pulsar spectra at low frequencies. We report mean flux density, spectral index, curvature, and low-frequency turnover-frequency measurements for 97 pulsars, including new measurements for 61 sources. Multifrequency profile widths are presented for all pulsars, including component spacing for 27 pulsars with two components. Polarized emission is detected from 27 of the sources (the largest sample at these frequencies) in multiple frequency bands, with one new detection. We also provide new timing solutions for five recently discovered pulsars. Low-frequency observations with the LWA are especially sensitive to propagation effects arising in the interstellar medium. We have made the most sensitive measurements of pulsar dispersion measures (DMs) and rotation measures, with median uncertainties of 2.9 × 10−4 pc cm−3 and 0.01 rad m−2, respectively, and can track their variations over almost a decade, along with other frequency-dependent effects. This allows for stringent limits on average magnetic fields, with no variations detected above ∼20 nG. Finally, the census yields some interesting phenomena in individual sources, including the detection of frequency- and time-dependent DM variations in B2217+47, and the detection of highly circularly polarized emission from J0051+0423.